Dialect accommodation and social identity: A sociolinguistic adaptation of Jakarta students in the Medan speech community - Achmad Hidir; Rahman Malik; Shelly Ruslina Hondro; Akmal Fauzan Nasution (TALENTA, 2025)
This study aims to explore the process of dialect adaptation in Medan by migrants from Jakarta, particularly among students at the University of North Sumatra. Using a descriptive qualitative method with interviews and observations, the study found that the dialectal differences between Jakarta and Medan created communication barriers during initial interactions, especially in terms of vocabulary, accent, and pronoun usage. However, migrants from Jakarta gradually adapted to the local dialect through intense social interactions and efforts to adjust to local cultural norms. This adaptation process accelerated social integration and helped migrants build stronger relationships with the Medan community. The study also shows that language change reflects migrants' efforts to be accepted in the local community. Dialect adaptation is not just about communication but also about the formation of social identity and acceptance of local culture. The study concludes that despite initial barriers, dialect adaptation in Medan becomes a crucial strategy in the social acculturation process that allows migrants to be accepted into their new environment.